Migrants’ motives and expectations for contacting out-of-hours primary care: a survey study - Keizer, Ellen (BMC Fam Pract, 2017)
BACKGROUND: Migrants are more likely to use out-of-hours primary care, especially for nonurgent problems. Their motives and expectations for help-seeking are as yet unknown. The objective of this study is to examine the motives and expectations of migrants for contacting out-of-hours primary care. METHODS: We used data from a survey study of 11,483 patients who contacted a General Practitioner (GP) cooperative in the Netherlands between 2009 and 2014 (response rate 45.6%). Logistic regression analysis was used to test differences in motives and expectations between non-western and western migrants and native Dutch patients. RESULTS: The main motives for contacting a GP cooperative for non-western and western migrants were an urgent need for contact with a GP (54.9%–52.4%), worry (49.3%–43.0%), and a need for medical information (21.3%–26.2%). These were also the most important motives for native Dutch patients. Compared to native Dutch patients, non-western migrants more often perceived an urgent need for a GP (OR 1.65; 99% CI 1.27–2.16), less often needed information (OR 0.59; 99% CI 0.43–0.81), and more often experienced problems contacting their own GP during office hours (OR 1.71; 99% CI 1.21–2.43). Western migrants also reported experiencing problems more often in contacting their own GP (OR 1.38; 99% CI 1.04–1.84). As well as for natives, most non-western and western migrants expected to see a doctor (46.2%–46.6%) or get advice (39.6%–41.5%). Non-western migrants expected more often to get physical examination (OR 1.53; 99% CI 1.14–2.04), and prescription (OR 1.37; 99% CI 1.00–1.88). We found no differences in expectations between western migrants and native Dutch patients. CONCLUSION: The main motives and expectations of migrants are similar to native Dutch patients, yet non-western migrants more often wanted action from the GP, e.g. examination or prescription, and less often passive forms of assistance such as giving information. At the same time they experience problems accessing their own GP. We recommend stimulation of self-care, education about the purpose of a GP cooperative, and examination and improvement of accessibility of daytime primary care.